Lung Ablation: Indications and Techniques - Tafti, Bashir Akhavan; Genshaft, Scott; Suh, Robert; Abtin, Fereidoun (Seminars in Interventional Radiology, 2019)
Lung ablation is ever more recognized since its initial report and use almost two decades ago. With technological advancements in thermal modalities, particularly microwave ablation and cryoablation, better identification of the cohort of patients who best benefit from ablation, and understanding the role of imaging after ablation, image-guided thermal ablation for primary and secondary pulmonary malignancies is increasingly recognized and accepted as a cogent form of local therapy.
Keywords: interventional radiology; lung; lung cancer; ablation